Neurodevelopmental origins of substance use disorders: Evidence from animal models of early‐life adversity and addiction. (25th April 2021) - Levis, Sophia C.; Baram, Tallie Z.; Mahler, Stephen V.
Abstract: Addiction is a chronic relapsing disorder with devastating personal, societal, and economic consequences. In humans, early‐life adversity (ELA) such as trauma, neglect, and resource scarcity are linked with increased risk of later‐life addiction, but the brain mechanisms underlying this link are still poorly understood. Here, we focus on data from rodent models of ELA and addiction, in which causal effects of ELA on later‐life responses to drugs and the neurodevelopmental mechanisms by which ELA increases vulnerability to addiction can be determined. We first summarize evidence for a link between ELA and addiction in humans, then describe how ELA is commonly modeled in rodents. Since addiction is a heterogeneous disease with many individually varying behavioral aspects that may be impacted by ELA, we next discuss common rodent assays of addiction‐like behaviors. We then summarize the specific addiction‐relevant behavioral phenotypes caused by ELA in male and female rodents and discuss some of the underlying changes in brain reward and stress circuits that are likely responsible. By better understanding the behavioral and neural mechanisms by which ELA promotes addiction vulnerability, we hope to facilitate development of new approaches for preventing or treating addiction in those with a history of ELA. Abstract : ELA perturbs multiple neurodevelopmental processes, including the development and maturation of reward and stress circuits. These alterations may lead to a variety of reward‐related behaviors associated with addiction. Importantly, the developmental trajectory from ELA to substance use is mediated by a complex multitude of interacting features, ultimately manifesting as a heterogeneous constellation of neurobiological and behavioral outcomes that increase risk for substance use disorder.